STATIC REGULATIONS OF UREA (CARBAMIDE) ADSORPTION BY WET AND DRIED PEAT - Oksana Matsuska; Olga Sukhorska; Jaroslaw Gumnitsky; Vira Sabadash (Environmental Problems, 2023)
The possibility and effectiveness of using a natural sorbent – peat from the Vereshchytsia-Yanivske deposit for treating agricultural wastewater with a high urea content – has been studied. The humidity and moisture content of the upland and lowland types of peat from this peatland were determined. Comparing these indicators made it possible to establish that the lowland peat has a significantly higher humidity and moisture content. The adsorption capacities of wet and dried types of peat for urea were studied and compared. The changes in urea concentration in aqueous solutions of the studied peat samples are presented by the corresponding curves. It was established that the lowland peat (dried samples) has higher sorption properties to urea when absorbed from the water environment than the upland type. In the adsorption of non-dried peat, curves were obtained, which show a gradual decrease in the concentration of urea in the solution, indicating the gradual filling of the active centres of peat with urea molecules. For pre-dried peat, rapid absorption of this pollutant is observed at the initial moments (approximately up to 10 minutes). The calculated maximum absorption capacities of dried peat species for urea show that the maximum absorption capacity of dry lowland peat is significantly higher than that of dry upland peat.